2023
DOI: 10.1002/adma.202300964
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineering Cell Membrane‐Coated BTO Nanoparticles for MMP2‐Activated Piezocatalysis‐Immunotherapy

Abstract: Tumor immunotherapy based on immune checkpoint blockade (ICB) still suffers from low host response rate and non‐specific distribution of immune checkpoint inhibitors, greatly compromising the therapeutic efficiency. Herein, cellular membrane stably expressing matrix metallopeptidase 2 (MMP2)‐activated PD‐L1 blockades is engineered to coat ultrasmall barium titanate (BTO) nanoparticle for overcoming the immunosuppressive microenvironment of tumors. The resulting M@BTO NPs can significantly promote the BTO's tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
(22 reference statements)
0
37
0
Order By: Relevance
“…7a). 70 In the piezoelectric degradation experiments, RhB in the M@BTO + US group was completely degraded after 100 min of US irradiation, indicating its excellent piezocatalytic ROS generation capacity. The oxygen generation of M@BTO in deoxygenated deionized water showed that M@BTO can piezocatalytically split water to produce oxygen, which can regulate the hypoxia of the TME.…”
Section: Biomaterials Science Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…7a). 70 In the piezoelectric degradation experiments, RhB in the M@BTO + US group was completely degraded after 100 min of US irradiation, indicating its excellent piezocatalytic ROS generation capacity. The oxygen generation of M@BTO in deoxygenated deionized water showed that M@BTO can piezocatalytically split water to produce oxygen, which can regulate the hypoxia of the TME.…”
Section: Biomaterials Science Reviewmentioning
confidence: 91%
“…69 Among these treatments, dynamic therapy can produce ROS to kill tumour cells, induce immunogenic cell death (ICD), release tumour-associated antigens (TAAs), and enhance tumour-specific immune responses. 70 However, dynamic…”
Section: Piezocatalytic Therapy Combined With Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Liang et al recently constructed M-𝛼PD-L1 NVs expressing a matrix metallopeptidase-2 (MMP-2)-activating lock masking on 𝛼PD-L1 (M-𝛼PD-L1) through ge-netic engineering, which can avoid 𝛼PD-L1 binding with normal tissues. [114] Furthermore, high MMP-2 expression in tumors cleaves the curling peptides of the MMP-2-activating lock, exposing 𝛼PD-L1 and blocking the PD-1-PD-L1 signaling axis at the cancer site, providing a promising strategy to enhance cancer immunotherapy. Similarly, Wang and co-workers obtained CMNs overexpressing PD-L1 through genetic engineering and coated them on PLGA NPs to prepare mesenchymal stem cell (MSC)-PD-L1 + NPs used to reduce immune-related adverse events induced by ICIs.…”
Section: Gcmns Expressing Anti-pd-l1mentioning
confidence: 99%
“…In recent years, cell membrane-coated nanoparticles have been extensively investigated for biomedical applications, such as drug delivery, , immunotherapy, biological neutralization , and phototherapy. By combining synthetic nanoparticle cores with naturally derived cell membrane layers, they inherit the highly complex functionalities of the source cells . These biomimetic nanoparticles possess numerous favorable advantages, including high biocompatibility, reduced toxicity, and specific targeting ability .…”
Section: Introductionmentioning
confidence: 99%